Does context matter? Voluntary work in long-term care - Laila Tingvold; Oddvar Førland (Nordic Journal of Social Research)
Introduction: Increased voluntary work in long-term care (LTC) is encouraged in white papers in Norway as well as in many other western states. This is due to the growth in the number of service recipients and a subsequent economic burden for the state. Voluntary work in nursing homes and home care services take place in different spatial contexts, but little attention has been paid to how the different contexts may potentially influence the possibilities for voluntary work. The aim of this study is to obtain new knowledge of the significance of context in recruitment of volunteers in LTC.